Steel for electric bit and preparation method thereof

By reducing the Mo content and optimizing components such as C, Si, Mn, Cr, Ni, etc., adding Nb elements, and combining a specific process flow, a low-cost, high wear resistance and high fatigue life electric batch steel is prepared. The existing electric batch steel has been solved, and the hardness and fatigue life have been improved.

CN119220911APending Publication Date: 2024-12-31ZENITH STEEL GROUP CORP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411283414.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing electric batch steel has high cost and insufficient wear resistance and fatigue life, making it difficult to reduce costs while maintaining performance. Mo is a precious alloy, reducing the Mo content can reduce costs but maintain performance.

Method used

By reducing the Mo content, optimizing components such as C, Si, Mn, Cr, Ni, etc., adding strong carbide elements such as Nb, and using appropriate process flow and key parameter control, a low-cost, high wear resistance, and high fatigue are prepared. Alloy tool steel with a lifetime ensures stable steel composition and high carbon segregation level.

Benefits of technology

The hardness is similar to S2M, the fatigue life is increased by 10-20%, the total cost is reduced, and the product is guaranteed to have high wear resistance and high fatigue life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005042365980000081
    Figure BDA0005042365980000081
  • Figure HDA0005042365990000011
    Figure HDA0005042365990000011
  • Figure HDA0005042365990000012
    Figure HDA0005042365990000012
Patent Text Reader

Abstract

The invention belongs to the technical field of steel and iron materials, and discloses steel for an electric bit and a preparation method of the steel. The steel comprises the following chemical components in percentage by weight: 0.62 percent to 0.69 percent of [C], 1.60 percent to 1.90 percent of [Si], 0.40 percent to 0.70 percent of [Mn], 0.40 percent to 0.58 percent of [Cr], 0.18 percent to 0.25 percent of [Mo], 0.20 percent to 0.30 percent of [Ni], 0.10 percent to 0.16 percent of [V], 0.020 percent to 0.030 percent of [Nb], 0.025 percent to 0.050 percent of [Al], less than or equal to 0.025 percent of [P], less than or equal to 0.020 percent of [S] and the balance of Fe and inevitable impurities. Aiming at the final application of the material, optimization design is conducted from the two aspects of components and the preparation method, and the produced steel is stable in component and high in carbon segregation control level and meets various performance requirements of users.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of steel material manufacturing, in particular to steel for electric screwdriver bits and a preparation method thereof. Background Art

[0002] A screwdriver bit is a typical alloy tool material. It is a thin wedge-shaped head that is inserted into the slot or notch of the screw head. It is combined with electric, pneumatic, manual and other tools to form a complete tool for tightening or loosening screws. It is divided into electric screwdriver bits, pneumatic screwdriver bits and hand tools. Among them, the one combined with electric tools is called an electric screwdriver bit. Compared with carbon tool steel, alloy tool steel has better hardenability, toughness, wear resistance and heat resistance, so it has a longer service life under more harsh service conditions. As a consumable part, the electric screwdriver bit becomes one of the weak links of the entire system, so the industry uses S2M material with the longest service life. Its chemical composition is: [C] 0.66-0.72%, [Si] 0.85-1.10%, [Mn] 0.40-0.55%, [Cr] 0.15-0.30%, [Ni] 0.10-0.20%, [Mo] 0.38-0.45%, [V] 0.15-0.25%, [P] ≤ 0.025%,

[0003] [S]≤0.020%, the rest being Fe and unavoidable impurities.

[0004] A high alloy tool steel wire rod CN11690801A, the chemical composition and mass percentage of the tool steel wire rod are: C: 0.60-0.70%, Si: 1.00-1.20%, Mn: 0.50-0.60%, P≤0.020%, S≤0.020%, Mo: 0.40-0.60%. Its composition is part of the S2M composition, which is incomplete, but generally speaking, it is still within the S2M composition category. A high-quality hypoeutectoid alloy tool steel wire and its production method CN110791717A discloses the chemical composition of the wire and its mass percentage content: C: 0.63-0.68%, Si: 1.10-1.20%, Mn: 0.60-0.70%, P≤0.025%, S≤0.025%, Cr: 0.30-0.40%, Mo: 0.50-0.60%, V: 0.20-0.30%, Ni: 0.10-0.20%, Cu≤0.25%, and the rest is iron and unavoidable impurities. Its chemical composition is highly similar to S2M.

[0005] A method for producing alloy hand tool steel wire rod without martensite structure CN114752858A discloses the chemical composition and mass percentage of the wire rod: C: 0.57% to 0.67%, Si: 1.11% to 1.20%, Mn: 0.25% to 0.33%, Cr: 0.31% to 0.37%, Mo: 0.23% to 0.29%, V: 0.10% to 0.14%, Ni: 0.04% to 0.06%, and trace amounts of P, S, O and N, and the rest are Fe and other inevitable impurities. Its chemical composition is highly similar to S2M.

[0006] A production method of tool steel wire CN117051308A discloses that the chemical composition of the steel is as follows: C: 0.65-0.75, Si: 1.00-1.40, Mn: 0.50-0.80, P≤0.025, S≤0.025, Cr: 0.30-0.60, Mo: 0.40-0.50, V: 0.10-0.25, Ni: 0.10-0.30, Nb: 0.010-0.030, and the rest is Fe and a small amount of impurities. Its chemical composition is highly similar to S2M. A method for manufacturing an energy-saving high-alloy tool steel wire rod with high bainite content CN114134399B discloses that the chemical composition of the wire rod includes C: 0.60-0.75%, Si: 1.00-1.50%, Mn: 0.40-0.70%, P: ≤0.020%, S: ≤0.020%, Cr: 0.10-0.50%, Mo: 0.30-0.70%, V: 0.15-0.30%, Ni: 0.05-0.40%, and the rest is Fe and unavoidable impurities. Its chemical composition is highly similar to S2M.

[0007] A production process of alloy tool steel wire rod with full bainite structure CN11690801A discloses that the chemical composition of the wire rod is C: 0.63-0.70, Si: 1.00-1.20, Mn: 0.40-0.60, P≤0.025, S≤0.025, Cr: 0.20-0.40, Ni: 0.12-0.30, Cu≤0.25, Al: 0.010-0.030, Mo: 0.40-0.50, V: 0.15-0.25, Nb: 0.010-0.025, and the rest is Fe and unavoidable impurities. Its chemical composition is highly similar to S2M.

[0008] A high-strength and high-wear-resistant alloy tool steel and its smelting method CN202310995781.1 publishes its chemical composition: C: 0.70%-0.76%, Si: 1.40%-1.60%, Mn: 0.50%-0.80%, Cr: 1.00%-1.20%, Ni: 0.20%-0.26%, V0.14%-0.20%, Al: 0.020%-0.040%, P≤0.025%, S≤0.020%, and the rest is Fe and unavoidable impurities. The composition of this steel is based on 60Si2CrV with an increased carbon content and a portion of Ni added. It is essentially a design idea for spring steel, and there is no description of the use and performance of the finished product.

[0009] In summary, the steel used for electric screwdriver bits is mainly S2M and a few adjustments to S2M, while a high-strength and high-wear-resistant alloy tool steel and its smelting method CN202310995781.1, which has been greatly adjusted, has no description of the use and performance of the finished product. So far, there are no other steel grades with the same use and performance as S2M, let alone products with the same use and performance as S2M but relatively low cost. Mo is a precious alloy, and the cost of every 0.01% content is 32.6 yuan / ton. If Mo drops by 0.20%, the cost can be reduced by 652 yuan / ton. Therefore, if an alternative product with the same use and performance as S2M but relatively low cost is developed, the product competitiveness will be greatly improved. There are two main properties of electric screwdriver bits. One is hardness, which requires 58-60HRC, which is a basic requirement and represents high wear resistance; the other is fatigue life, which is related to the service life in actual use-reducing the number of replacement bits and improving work efficiency.

[0010] During the fatigue test of the product, in addition to the steel composition, the segregation level of the steel directly affects the downstream processing technology and the various properties of the final product, namely the screwdriver bit. For example, the center segregation is easy to form a hard and brittle martensite structure, which leads to problems such as brittle fracture during transportation or increased downstream spheroidization costs. At the same time, segregation also reduces the fatigue life of the screwdriver bit, so it is very necessary to improve the carbon segregation level of the product. Therefore, according to the purpose of the product, the composition and process should be reasonably designed according to the performance of the electric screwdriver bit to meet the requirements of high wear resistance (high hardness) and high fatigue life during use. Summary of the invention

[0011] The purpose of the present invention is to provide a steel for electric screwdriver bits and a preparation method thereof. Based on the existing S2M alloy tool steel composition, by reducing the Mo content, optimizing the components such as C, Si, Mn, Cr, Ni, adding strong carbide elements such as Nb, and adopting a suitable process flow and control of key parameters, a low-cost, high-wear-resistant, and high-fatigue-life alloy tool steel and a preparation method thereof are provided, which can ensure that the composition of the produced steel is stable and the carbon segregation control level is high. Compared with the screwdriver bits made of S2M, the hardness is similar and the fatigue life is 10-20% higher.

[0012] In the composition design of the present invention, the Mo content is greatly reduced, so the content of Si, Cr, Ni and other alloys is increased; compared with the cost reduction brought about by reducing the Mo content, the cost increase brought about by increasing the content of Si, Cr, Ni and other alloys is small, so the total cost of the patented steel will be greatly reduced.

[0013] In order to achieve the above-mentioned object, the composition of the steel for an electric screwdriver bit of the present invention is calculated by weight percentage:

[0014] [C] 0.62% ~ 0.69%, [Si] 1.60% ~ 1.90%, [Mn] 0.40% ~ 0.70%, [Cr] 0.40% ~ 0.58%, [Mo] 0.18% ~ 0.25%, [Ni] 0.20% ~ 0.30%, [V] 0.10% ~ 0.16%, [Nb] 0.020% ~ 0.030%, [Al] 0.025% ~ 0.050%, [P] ≤ 0.025%, [S] ≤ 0.020%, and the rest is Fe and unavoidable impurities.

[0015] The preferred chemical composition is as follows by weight: [C] 0.63% to 0.67%, [Si] 1.70% to 1.85%,

[0016] [Mn] 0.50%~0.60%, [Cr] 0.42%~0.55%, [Mo] 0.19%~0.23%, [Ni] 0.21%~0.24%, [V] 0.11%~0.14%, [Nb] 0.020%~0.025%, [Al] 0.025%~0.035%, [P]≤0.015%, [S]≤0.010%, and the rest is Fe and unavoidable impurities.

[0017] The material prepared by the present invention is used to make screwdriver bits, which has extremely strict requirements on the hardness and fatigue life of the final product. Under the condition of stable heat treatment performance, the key factor affecting the final performance of the product is the design of chemical composition. In addition to being mainly affected by a certain element, a certain performance is also affected by multiple elements at the same time. Therefore, the rational design of multiple elements needs to be considered according to the purpose of the product. Reasons for the composition design of the present invention:

[0018] [C] is the most effective element for improving strength and hardness in steel, and has a significant solid solution strengthening effect. However, if the content is too high, large carbides will be formed, which will sharply reduce the toughness of the steel. If the carbon content is low, the hardness of the steel will be low and the wear resistance will be poor. The preferred content in this invention is 0.65% to 0.67%. [Si] improves the hardness and strength of ferrite and austenite, and its effect is stronger than that of Mn, Ni, Cr, W, Mo, V, etc. It significantly improves the elastic limit, yield strength and yield strength ratio of steel, and improves fatigue strength and fatigue ratio. Adding a certain amount of silicon to quenched and tempered steel, silicon combined with chromium, molybdenum, etc. can improve the anti-oxidation, corrosion resistance, heat resistance and other properties. In addition, silicon is also used as a commonly used deoxidizer, partially replacing aluminum for deoxidation. The preferred content in this invention is 1.75% to 1.85%.

[0019] [Mn] can play a role in solid solution strengthening, improve the strength of steel, and can significantly improve the hardenability of steel, improve the hot working performance of steel, and can weaken and eliminate the adverse effects of sulfur. However, too high manganese content can easily increase the temper brittleness of steel. The preferred content of the present invention is 0.50-0.60%.

[0020] [Cr] can improve the strength, hardness, wear resistance and corrosion resistance of steel, and can also improve the steel's oxidation resistance and corrosion resistance. However, too high a content will reduce the toughness of the steel. The preferred content of the present invention is 0.42% to 0.55%.

[0021] [Ni] strengthens ferrite and refines and increases pearlite, thereby increasing the strength of steel without significantly affecting the plasticity of steel. The carbon content of nickel-containing steel can be appropriately reduced, thereby improving toughness and plasticity. It increases the fatigue resistance of steel, reduces the sensitivity of steel to notches, and has rust prevention and heat resistance at high temperatures. The preferred content of the present invention is 0.21% to 0.24%.

[0022] [Mo] has a solid solution strengthening effect on ferrite and is a strong carbide forming element. It can improve the hardenability of steel and combine with C element to form special carbides, improve the stability of carbides, and thus improve the strength of steel. Mo plays a favorable role in improving the ductility, toughness and wear resistance of steel. Because molybdenum increases the softening and recovery temperature after deformation strengthening, as well as the recrystallization temperature, and strongly improves the creep resistance of ferrite, effectively inhibits the aggregation of cementite at 450-600°C, and promotes the precipitation of special carbides, it becomes the most effective alloy element for improving the thermal strength of steel. In the present invention, it is preferably 0.19% to 0.23%.

[0023] [V] can refine the grain size of the structure and improve the strength and toughness, but too high a content can easily cause defects such as surface cracks. The simultaneous addition of chromium, nickel and vanadium elements can refine the grain size, improve the strength, wear resistance, hardness, red hardness, corrosion resistance and toughness of tool steel, improve the fatigue resistance of steel, and reduce the low-temperature brittle transition temperature of steel. The preferred content of the present invention is 0.11% to 0.14%.

[0024] [Nb] is a strong carbide element that can form stable carbides and carbonitrides with carbon and nitrogen in steel, and mainly plays the role of refining grains and improving strength. Niobium can also achieve dispersed distribution of precipitates by inducing precipitation and controlling the cooling rate, thereby adjusting the toughness level of steel within a wider range. The preferred content of the present invention is 0.020% to 0.025%.

[0025] [Al] is a key element for deoxidation. It also refines grains and improves impact toughness. Aluminum also has antioxidant and corrosion resistance. When used in combination with chromium and silicon, it can significantly improve the high-temperature non-scaling and high-temperature corrosion resistance of steel. However, too high a content will affect the hot working and welding properties of steel. The preferred content in the present invention is 0.025% to 0.035%.

[0026] [P] and [S] are generally harmful elements in steel. In the present invention, [P]≤0.015% and [S]≤0.010% are preferred.

[0027] The present invention also provides a preparation method of a steel for electric screwdriver bits, including converter smelting, LF refining, RH vacuum treatment, large square billet continuous casting, billet production, billet finishing, billet heating, wire rod rolling, wire rod controlled cooling, etc. The steps are as follows:

[0028] (1) Converter smelting: The converter is charged with 80% molten iron and 20% scrap steel by weight. High carbon drawing operation is adopted at the end of smelting. The tapping [C] is greater than 0.05%, the tapping [P] is less than 0.015%, and the tapping temperature is greater than 1600°C. Deoxidizer, alloy, carburizer and slag are added respectively 30s after tapping. Double gear operation is adopted at the end of tapping. After tapping, the molten steel is hoisted to LF for refining.

[0029] (2) LF refining: In the early stage of LF, appropriate amounts of lime and fluorite (cryolith) are added in batches depending on the fluidity of the slag; calcium carbide, silicon carbide or aluminum particles are used for deoxidation and desulfurization in the early and middle stages of refining. In the early stage of refining, an appropriate amount of aluminum wire can be supplemented depending on the Al content of the molten steel. Supplementary feeding is only allowed once to ensure the target aluminum content of the finished product.

[0030] (3) RH vacuum treatment: After the molten steel reaches the RH station, the ladle is lifted to the vacuum tank and the vacuum cycle begins. The lifting gas is argon and is controlled at 105-125 Nm 3 / h, when the vacuum degree is less than 67Pa, maintain the pressure for 15min and then break the air, take the molten steel sample, and adjust the Al content by feeding aluminum wire according to the sample analysis results, and then feed 50-100m calcium wire for modification treatment, and after soft blowing for 15-20min, the molten steel is hoisted to the continuous casting for casting.

[0031] (4) Continuous casting of large square billets: The baking temperature of the tundish is greater than 1100℃ before continuous casting. After the baking of the tundish stops, argon gas is flushed inside for 3-5 minutes. After the casting starts, the surface of the steel liquid in the tundish is protected during the entire process. The tundish adopts an integral nozzle for casting. The casting superheat is controlled at 20-30℃. After each furnace casting, steel slag is left in the ladle. The continuous casting speed is controlled at 0.90m / min, the temperature difference of the first cooling water return water is controlled at 4-6℃, the water volume of the second cooling is 0.20L / kg, the crystallizer and the end electromagnetic stirring are turned on, and the solidification end is lightly pressed down. The large square billets are slowly cooled in the pit, and the pit temperature is greater than 500℃. The pit can be taken out after the insulation time is greater than 42 hours.

[0032] (5) Billet production: 280mm×329mm cast billets are diffused for a long time at high temperature in a heating furnace with a total length of 51m, and then billeted into 160mm×160mm rolled billets. How to stack them to avoid wind and cool them?

[0033] (6) Billet finishing: 160mm×160mm billet is finished and peeled, with a single-side peeling depth of 2mm, and then surface flaw detection is performed. [(7) Billet heating: 160mm×160mm billet is heated at low temperature in a high-speed wire heating furnace, with a heating temperature of 1050~1100℃, a heating time of 90~120 minutes, and a rolling temperature of 950~1000℃.

[0034] (8) Wire rod rolling: The billet is rolled into wire rod through rough rolling, intermediate rolling, pre-finishing rolling and finishing rolling, and then enters the laying machine. The finishing rolling temperature is 880℃~920℃

[0035] (9) The wire rod spinning temperature is 750-780°C. After spinning, controlled cooling is carried out and the wire rod is rolled.

[0036] Furthermore, in the step (4), the nominal cross-sectional size of the large square billet is 300 mm×325 mm, the temperature difference between the cooling water and the electromagnetic stirring water is 4-6°C; the electromagnetic stirring of the crystallizer is 290-310 A, and the frequency is 1.8-2.2 Hz; the end electric stirring F-EMS current is 300-310 A, and the frequency is 6-6.5 / HZ; and the 1# to 5# rollers are used for pressing at the end of solidification, and the pressing amounts are 2 mm, 4 mm, 7 mm, 5 mm, and 3 mm respectively, and the total pressing amount is 21 mm.

[0037] Furthermore, the billet heating furnace in step (5) is divided into five temperature control sections, namely, a preheating section, a heating section I, a heating section II, a soaking section I, and a soaking section II; the heating temperatures are ≤800°C, 1150°C-1220°C, 1180°C-1250°C, 1210°C-1250°C, and 1210°C-1250°C respectively; the rolling temperature is 1080-1180°C, and the total heating time is 823 minutes-975 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a low-magnification photograph of a longitudinal section of the continuous casting slab of Example 1;

[0039] Figure 2 This is a low-magnification photograph of the longitudinal section of the rolled billet of Example 1;

[0040] Figure 3 Batch bit fatigue life testing machine. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with a production example of steel for electric screwdriver bits and a preparation method thereof, wherein the conditions not limited thereto are conventional conditions.

[0042] Example 1

[0043] (1) Converter smelting: The converter was loaded with 115 tons of molten iron and 25 tons of scrap steel in a weight ratio, with molten iron containing [Si]0.65%, [P]0.060%, [S]0.022%, and a temperature of 1348°C. At the end of smelting, the tapping temperature was 1629°C, with a [C]0.11% and a [P]0.011% respectively. The tapping temperature was 5 min, and 130 kg of aluminum blocks were added 30 s after tapping. After adding the aluminum blocks, various alloys were added, and then 400 kg of carburizer was added. Finally, 550 kg of lime and 300 kg of slag-reducing agent were added. At the end of tapping, a slide plate and a slag stopper were used to stop the slag. After tapping, the molten steel was hoisted to LF for refining.

[0044] (2) LF refining: LF refining sampling is done before entering the station. 50kg Al pellets and 80kg silicon carbide are used for deoxidation and desulfurization. After 15 minutes of smelting, silicon carbide is used for slag preservation, that is, a small amount of silicon carbide is added evenly on the slag surface to ensure that the slag surface is in a reducing atmosphere. Alloy is added according to the analysis results of the incoming samples, and the temperature is adjusted to 1585℃. The argon stirring intensity is 70L / min throughout the refining process. In the early stage of refining, an appropriate amount of aluminum wire can be fed according to the Al content of the molten steel. Only one feeding is allowed to ensure the target aluminum content of the finished product.

[0045] (3) RH vacuum treatment: After the molten steel reaches the RH station, the ladle is lifted to the vacuum tank and the vacuum cycle begins. The lifting gas is argon and is controlled at 105-125 Nm 3 / h, when the vacuum degree is less than 67Pa, maintain the pressure for 15min and then break the air, take the molten steel sample, and adjust the Al content by feeding aluminum wire according to the sample analysis results, and then feed 50-100m calcium wire for modification treatment, and after soft blowing for 15-20min, the molten steel is hoisted to the continuous casting for casting.

[0046] (4) Continuous casting of large square billets: The nominal cross-sectional dimensions of large square billets are 300 mm × 320 mm. The baking temperature of the tundish is greater than 1100 °C before continuous casting. After the baking of the tundish stops, argon gas is flushed inside for 3 to 5 minutes. After the casting starts, the surface of the steel liquid in the tundish is protected throughout the casting process. The tundish is cast with an integral nozzle. The casting superheat is controlled at 20 to 30 °C. At the end of each furnace casting, slag is left in the ladle. The continuous casting speed is controlled at 0.90m / min, the return water temperature difference of the first cooling water is controlled at 4-6℃, the water volume of the second cooling water is 0.20L / kg, the crystallizer and the end electromagnetic stirring are turned on: the crystallizer electromagnetic stirring is 290-310A, the frequency is 1.8-2.2Hz; the end electric stirring F-EMS current is 300-310A, the frequency is 6-6.5 / HZ; the end of solidification adopts light pressure reduction, and the pressure reduction process is: 1#~5# rollers are pressed, and the pressure reduction is 2mm, 4mm, 7mm, 5mm respectively, and the total pressure reduction of 3mm is 21mm. The large square billet adopts slow cooling in the pit, the pit temperature is greater than 500℃, and the heat preservation time is greater than 42 hours before it can be taken out of the pit.

[0047] (5) Billet production: 280mm×329mm ingots are diffused at high temperature for a long time in a heating furnace with a total length of 51m, and then billeted into 160mm×160mm rolled billets, which are then stacked and cooled in a windproof manner. The billet heating furnace is divided into 5 temperature control sections, namely preheating section, heating section I, heating section II, soaking section I, and soaking section II; the heating temperatures are 780℃, 1170℃-1200℃, 1200℃-1240℃, 1230℃-1250℃, and 1225℃-1245℃ respectively; the rolling temperature is 1080-1180℃, and the total heating time is 955 minutes. The cross-section of the large square billet is 280mm×329mm, and the carbon segregation index of the billet is 1.081( Figure 1 ), the carbon segregation index of 160mm×160mm billet is 1.056( Figure 2 ).

[0048] (6) Billet finishing: 160mm×160mm billet is finished and peeled, with a single-side peeling depth of 2mm, and then surface flaw detection is performed. (7) Billet heating: 160mm×160mm billet is heated at low temperature in a high-speed wire heating furnace, with a heating temperature of 1050~1100℃, a heating time of 100~110 minutes, and a rolling temperature of 950~1000℃.

[0049] (8) Wire rod rolling: The billet is rolled into wire rod through rough rolling, intermediate rolling, pre-finishing rolling and finishing rolling, and then enters the laying machine. The finishing rolling temperature is 880℃~920℃

[0050] (9) The wire rod spinning temperature is 760-770°C. After spinning, controlled cooling is carried out and the wire rod is rolled.

[0051] Example 2

[0052] The chemical composition of the steel for the electric screwdriver bit is different from that in Example 1, and the rest is the same as that in Example 1.

[0053] Example 3

[0054] The chemical composition of the steel for the electric screwdriver bit is different from that in Example 1, and the rest is the same as that in Example 1.

[0055] Comparative Example 1

[0056] Compared with Example 1, Comparative Example 1 is that the light pressing process in step 4 of Example 1 is deleted, and other conditions are the same as those of Example 1.

[0057] Comparative Example 2

[0058] Compared with Example 1, Comparative Example 2 is different from Example 1 in that the high temperature diffusion process in step 5 of Example 1 is removed, and other conditions are the same as those of Example 1.

[0059] Comparative Example 3

[0060] Compared with Example 1, Comparative Example 3 is that the carbon content of Example 1 is adjusted to 0.60%, and other conditions are the same as those of Example 1.

[0061] Comparative Example 4

[0062] Compared with Example 1, Comparative Example 4 is that the carbon content of Example 1 is adjusted to 0.72%, and other conditions are the same as those of Example 1.

[0063] Comparative Example 5

[0064] Compared with Example 1, Comparative Example 5 is that the Si content of Example 1 is adjusted to 1.40%, and other conditions are the same as those of Example 1.

[0065] Comparative Example 6

[0066] Compared with Example 1, Comparative Example 6 is that the Ni content of Example 1 is adjusted to 0.12%, and other conditions are the same as those of Example 1.

[0067] Comparative Example 7

[0068] Compared with Example 1, Comparative Example 7 is that the Cr content of Example 1 is adjusted to 0.23%, and other conditions are the same as those of Example 1.

[0069] Comparative Example 8

[0070] Compared with Example 1, Comparative Example 8 is that the Mo content of Example 1 is adjusted to 0.12%, and other conditions are the same as those of Example 1.

[0071] Comparative Example 9

[0072] Compared with Example 1, Comparative Example 9 is that the Nb content of Example 1 is adjusted to 0, and other conditions are the same as those of Example 1.

[0073] Comparative Example 10

[0074] In Comparative Example 10, compared with Example 1, the Si content of Example 1 is adjusted to 1.40%, the Ni content is increased to 0.40%, and the other conditions are the same as those of Example 1.

[0075] Comparative Example 11

[0076] Compared with Example 1, Comparative Example 11 is that the Si content of Example 1 is adjusted to 1.40%, and the Mo content is increased to 0.35%. Other conditions are the same as those of Example 1.

[0077] The smelting compositions of the embodiments of the present invention and the comparative examples are shown in Table 1:

[0078] Table 1 Melting composition of examples and comparative examples (wt / %)

[0079] chemical composition C Si Mn Cr Ni V Mo P S Nb Al Example 1 0.66 1.77 0.55 0.48 0.22 0.12 0.20 0.015 0.008 0.021 0.031 Example 2 0.66 1.79 0.54 0.45 0.22 0.13 0.20 0.013 0.009 0.022 0.032 Example 3 0.65 1.79 0.55 0.46 0.23 0.12 0.21 0.013 0.008 0.022 0.029 Comparative Example 1 0.66 1.77 0.55 0.48 0.22 0.12 0.20 0.015 0.008 0.021 0.031 Comparative Example 2 0.66 1.77 0.55 0.48 0.22 0.12 0.20 0.015 0.008 0.021 0.031 Comparative Example 3 0.60 1.78 0.55 0.45 0.23 0.12 0.20 0.014 0.009 0.022 0.028 Comparative Example 4 0.72 1.78 0.54 0.48 0.22 0.13 0.21 0.015 0.007 0.020 0.031 Comparative Example 5 0.67 1.40 0.56 0.46 0.22 0.12 0.21 0.014 0.008 0.021 0.028 Comparative Example 6 0.65 1.77 0.54 0.47 0.12 0.13 0.20 0.013 0.006 0.022 0.029 Comparative Example 7 0.66 1.79 0.55 0.23 0.23 0.12 0.20 0.014 0.008 0.020 0.031 Comparative Example 8 0.67 1.78 0.54 0.46 0.21 0.13 0.12 0.015 0.009 0.021 0.029 Comparative Example 9 0.67 1.77 0.53 0.45 0.22 0.13 0.20 0.013 0.007 / 0.029 Comparative Example 10 0.66 1.40 0.53 0.48 0.40 0.12 0.21 0.012 0.008 0.022 0.032 Comparative Example 11 0.66 1.40 0.54 0.47 0.22 0.13 0.35 0.012 0.007 0.021 0.031

[0080] The products of the embodiments of the present invention, the comparative examples and S2M are selected from ¢8mm hot-rolled wire rods, which are shot blasted, spheroidized annealed at 760℃, pickled, and drawn into H6.3mm fine wires. The final products are made into PH2*50mm cross screwdriver bits. The hardness and fatigue life of the corresponding screwdriver bits are tested under the same conditions. The specific data are shown in Table 2:

[0081] Table 2 Performance parameters of the embodiments and comparative examples

[0082]

[0083] Note: 1. Hardness test: in accordance with GB / T230.1-2018 (Metallic Materials Rockwell Hardness Test Part 1 Test Method).

[0084] 2. Fatigue life test: The fatigue life test is carried out in a PB-6030 fatigue life tester under a static torque of 10.3Nm using a forward and reverse rotation method until the bit breaks. The number of rotations automatically displayed by the equipment is the fatigue life (see Appendix Figure 3 Batch fatigue life testing machine).

[0085] It can be seen from the above table data that the various performance indicators of the embodiments fully meet the performance indicator requirements of S2M, and are not much different from the actual detection values ​​of S2M; the carbon segregation index of the cast and rolled billets of Comparative Examples 1 and 2 is relatively high. Although the hardness is not much different from S2M, the fatigue life is relatively low, and can only be used for separate manual or pneumatic tools, and cannot be used for electric combination tools that require fatigue life on automated production lines; the data of Comparative Examples 3 to 8 show that when the Mo content is reduced to 0.18% to 0.25%, Si, Cr, and Ni must be increased to the composition range of the patented steel to ensure the performance of the screwdriver bit, and the C content must be slightly lower than that of S2M; if the Mo content is further reduced to about 0.12%, the performance of the screwdriver bit cannot be guaranteed.

[0086] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification made to the above embodiments based on the technical essence of the present invention is included in the protection scope of the present invention.

Claims

1. A steel for electric screwdriver bits, characterized in that: The chemical composition of the steel for an electric screwdriver bit is, by weight percentage, [C] 0.62% to 0.69%, [Si] 1.60% to 1.90%, [Mn] 0.40% to 0.70%, [Cr] 0.40% to 0.58%, [Mo] 0.18% to 0.25%, [Ni] 0.20% to 0.30%, [V] 0.10% to 0.16%, [Nb] 0.020% to 0.030%, [Al] 0.025% to 0.050%, [P] ≤ 0.025%, [S] ≤ 0.020%, and the rest is Fe and unavoidable impurities.

2. The steel for electric screwdriver bits and the method for preparing the same as claimed in claim 1, characterized in that: The chemical composition of the steel for an electric screwdriver bit is calculated by weight percentage as follows: [C] 0.63% to 0.67%, [Si] 1.70% to 1.85%, [Mn] 0.50% to 0.60%, [Cr] 0.42% to 0.55%, [Mo] 0.19% to 0.23%, [Ni] 0.21% to 0.24%, [V] 0.11% to 0.14%, [Nb] 0.020% to 0.025%, [Al] 0.025% to 0.035%, [P] ≤ 0.015%, [S] ≤ 0.010%, and the rest is Fe and unavoidable impurities.

3. The method for preparing steel for electric screwdriver bits according to claim 1 or 2, characterized in that: The preparation method comprises converter smelting, LF refining, RH vacuum treatment, bloom continuous casting, bloom production, bloom finishing, bloom heating, wire rod rolling, and wire rod controlled cooling; The continuous casting conditions of large square billets are as follows: the continuous casting speed is controlled at 0.90m / min, the temperature difference of the first cooling water return water is controlled at 4-6℃, the water volume of the second cooling water is 0.20L / kg, the electromagnetic stirring of the crystallizer and the electromagnetic stirring at the end are turned on, the end of solidification is lightly pressed down, the large square billets are slowly cooled in the pit, the pit temperature is greater than 500℃, and the heat preservation time is greater than 42 hours before they can be taken out of the pit; The production conditions for billet opening are as follows: the billet is diffused at high temperature for a long time in a heating furnace, and after rolling, the billet is collected at a temperature of 400℃-500℃, and is stacked and cooled in the windproof place after rolling.

4. The method for preparing steel for electric screwdriver bits according to claim 3, characterized in that: The crystallizer has an electromagnetic stirring current of 290-310A and a frequency of 1.8-2.2 Hz; the end electromagnetic stirring current is 300-310A and a frequency of 6-6.5 Hz.

5. The method for preparing steel for electric screwdriver bits according to claim 3, characterized in that: At the end of solidification, 1# to 5# rollers are used for light pressing, with the pressing amounts being 2mm, 4mm, 7mm, 5mm, and 3mm respectively, with a total pressing amount of 21mm.

6. The method for preparing steel for electric screwdriver bits according to claim 3, characterized in that: Billet heating: The billet is heated at low temperature in a high-speed wire heating furnace, the heating temperature is 1050-1100℃, the heating time is 90-120 minutes, and the starting rolling temperature is 950-1000℃; Wire rod rolling: The billet is rolled into wire rod through rough rolling, intermediate rolling, pre-finishing rolling and finishing rolling, and then enters the laying machine, and the finishing rolling temperature is 880℃~920℃.

7. The method for preparing steel for electric screwdriver bits according to claim 3, characterized in that: The long-term high-temperature diffusion is a billet heating furnace divided into five temperature control sections, namely, preheating section, heating section I, heating section II, soaking section I, soaking section II; the heating temperatures are ≤800°C, 1150°C-1220°C, 1180°C-1250°C, 1210°C-1250°C, 1210°C-1250°C, respectively; the rolling temperature is 1080-1180°C, and the total heating time is 823 minutes-975 minutes.